Pharmacomicrobiology of Methotrexate in Rheumatoid Arthritis: Gut Microbiome as Predictor of Therapeutic Response - Yan, Huanhuan; Su, Rui; Xue, Hongwei; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a disabling autoimmune disease with invasive arthritis as the main manifestation and synovitis as the basic pathological change, which can cause progressive destruction of articular cartilage and bone, ultimately leading to joint deformity and loss of function. Since its introduction in the 1980s and its widespread use in the treatment of RA, low-dose methotrexate (MTX) therapy has dramatically changed the course and outcome of RA treatment. The clinical use of this drug will be more rational with a better understanding of the pharmacology, anti-inflammatory mechanisms of action and adverse reaction about it. At present, the current clinical status of newly diagnosed RA is that MTX is initiated first regardless of the patients’ suitability. But up to 50% of patients could not reach adequate clinical efficacy or have severe adverse events. Prior to drug initiation, a prognostic tool for treatment response is lacking, which is thought to be the most important cause of the situation. A growing body of studies have shown that differences in microbial metagenomes (including bacterial strains, genes, enzymes, proteins and/or metabolites) in the gastrointestinal tract of RA patients may at least partially determine their bioavailability and/or subsequent response to MTX. Based on this, some researchers established a random forest model to predict whether different RA patients (with different gut microbiome) would respond to MTX. Of course, MTX, in turn, alters the gut microbiome in a dose-dependent manner. The interaction between drugs and microorganisms is called pharmacomicrobiology. Then, the concept of precision medicine has been raised. In this view, we summarize the characteristics and anti-inflammatory mechanisms of MTX and highlight the interaction between gut microbiome and MTX aiming to find the optimal treatment for patients according to individual differences and discuss the application and prospect of precision medicine.